2022
DOI: 10.1088/1748-9326/ac5207
|View full text |Cite
|
Sign up to set email alerts
|

Growth rings show limited evidence for ungulates’ potential to suppress shrubs across the Arctic

Abstract: Global warming has pronounced effects on tundra vegetation, and rising mean temperatures increase plant growth potential across the Arctic biome. Herbivores may counteract the warming impacts by reducing plant growth, but the strength of this effect may depend on prevailing regional climatic conditions. To study how ungulates interact with temperature to influence growth of tundra shrubs across the Arctic tundra biome, we assembled dendroecological data from 20 sites, comprising 1,153 individual shrubs and 22,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…3). Across the arctic tundra biome, local richness of large herbivores typically ranges from 0 to 2 species ( 19 ), so the magnitude of the increase in herbivore diversity over the course of this experiment is comparable to extant biome-wide variation in large herbivore diversity (but not density, which is comparatively low at this site) ( 24 , 31 ).…”
Section: Mediation Of Tundra Diversity Responses To the Experiments B...mentioning
confidence: 97%
“…3). Across the arctic tundra biome, local richness of large herbivores typically ranges from 0 to 2 species ( 19 ), so the magnitude of the increase in herbivore diversity over the course of this experiment is comparable to extant biome-wide variation in large herbivore diversity (but not density, which is comparatively low at this site) ( 24 , 31 ).…”
Section: Mediation Of Tundra Diversity Responses To the Experiments B...mentioning
confidence: 97%
“…Besides rising temperature, we also hypothesize that the growth rate increase over the last century may have been triggered by rising CO 2 concentrations and changing competition level. We tend to exclude any anthropogenic influence through land abandonment, as none of the species studied is grazed by livestock, which probably influences the establishment of woody plants (Améztegui et al, 2010;Galop et al, 2011), but not the radial growth of already established individuals (Vuorinen et al, 2022). Yet, uncertainties remain about possible changes in the level of competition between plants in a context where shrubs have been favored over herbaceous species in the past.…”
Section: Growth Trendsmentioning
confidence: 99%
“…Herbivories were anticipated to slow, stop, or even reverse shrub expansion resulting from climate warming, e.g., [105,106]. Field exclusion experiments showed that releases from both small and large herbivories may change the plant species composition of tundra communities [104,107].…”
Section: Herbivorymentioning
confidence: 99%
“…For instance, a 20-year exclosure experiment on tundra vegetation in Scandinavia and Alaska indicated that mammalian herbivories helped in reducing the leaf area index (LAI), NDVI, and abundance of vascular plants, and large herbivories aided in lowering plant statures, while small herbivories assisted in boosting plant species diversity [104]. A 3-year exclosure experiment documented that the phytomass of deciduous shrubs, forbs, and silica-poor grasses increased by 40-50% in the absence of ungulate (e.g., reindeer) and small rodent herbivores (e.g., voles and lemmings) [106]. The impacts of herbivory on tundra shrub may depend on experiment periods, landscapes, characteristics of herbivore species and herbivory density in the plant community [106,108].…”
Section: Herbivorymentioning
confidence: 99%
See 1 more Smart Citation